Experimental study of electrical resistivity in tetrahydrofuran hydrate-bearing sediments - Xian, Fei; Chen, Ming; Li, Min; Dai, Qin; Xia, Fujun; Lee, Zizeng; Hou, Jian; Liu, XueFeng (Frontiers in Earth Science, 2025)
Natural gas hydrates, solid crystalline structures formed by the combination of natural gas and water molecules under high-pressure and low-temperature conditions, are regarded as a promising clean energy source. Electrical resistivity serves as a fundamental petrophysical parameter for quantifying natural gas hydrate saturation in sand-dominated sediments, with its sensitivity to pore-filling hydrate morphology and distribution patterns. An integrated experimental system combining in-situ CT scanning and resistivity measurement was developed to investigate tetrahydrofuran (THF) hydrate formation dynamics in quartz sand sediments. We prepared four distinct THF solutions to represent different hydrate formation regimes, lowered the temperature within a reactor containing quartz grains, and continuously monitored the electrical resistivity of the sediments during the hydrate formation. Additionally, CT scanning was used to acquire three-dimensional grayscale images at varying hydrate saturation. The experimental resistivity data revealed pronounced deviations from classical Archie’s equation, demonstrating complex behavior between the resistivity index and water saturation. The CT scan images demonstrate a pronounced salting-out effect during the hydrate formation process. The precipitation of dissolved salts significantly increased the salinity of formation water, resulting in a corresponding decrease in resistivity due to enhanced ionic conductivity. The phenomenon significantly impedes hydrate formation kinetics, causing a substantial divergence between the measured hydrate saturation and the thermodynamic equilibrium prediction. When temperature effects and salt precipitation phenomena are properly accounted for, the resistivity index-water saturation relationship exhibits excellent agreement with Archie’s law, enabling reliable estimation of hydrate saturation in quartz-dominated sediments.